2020
DOI: 10.1021/acs.oprd.0c00184
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis of 7-Azaindazole by a Diels–Alder Cascade and Associated Process Safety

Abstract: Although pyrimidines are not among the most reactive partners in intramolecular inverse-electron demand [4ps+2ps] reactions with alkynes, they could be activated under mild and practical conditions, leading to fused nitrogen-containing heterocycles. We report an optimized synthesis of a 5-iodo-7-aza-indazole by a one-pot Diels-Alder cascade that starts from a pyrimidine substituted in the 2-position by an (alkynyl)hydrazone. The safety of the process and the environmental impact were thoroughly evaluated. Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…After a short optimization, we found that the combination of NaH in DMSO was compatible with a wide variety of nucleophiles, securing a good solubility of the system, a full conversion and still a perfect regio‐ and stereoselectivity. Several nitrogen‐containing heteroaromatic compounds can easily be introduced on SF 5 ‐alkynes such as indole ( 3 ab ), benzotriazole ( 3 ad ), tetrazole ( 3 ae ), carbazole ( 3 af ), 6‐ or 7‐aza‐indazoles ( 3 ag‐h , 3 dh ) [23] with yields ranging from 43 to 73 %. In addition, the 2‐SF 5 ‐indole [21] is also a competent nucleophile in these conditions and provide compound 3 ac in 50 % yield bearing two SF 5 motifs.…”
Section: Resultsmentioning
confidence: 99%
“…After a short optimization, we found that the combination of NaH in DMSO was compatible with a wide variety of nucleophiles, securing a good solubility of the system, a full conversion and still a perfect regio‐ and stereoselectivity. Several nitrogen‐containing heteroaromatic compounds can easily be introduced on SF 5 ‐alkynes such as indole ( 3 ab ), benzotriazole ( 3 ad ), tetrazole ( 3 ae ), carbazole ( 3 af ), 6‐ or 7‐aza‐indazoles ( 3 ag‐h , 3 dh ) [23] with yields ranging from 43 to 73 %. In addition, the 2‐SF 5 ‐indole [21] is also a competent nucleophile in these conditions and provide compound 3 ac in 50 % yield bearing two SF 5 motifs.…”
Section: Resultsmentioning
confidence: 99%
“…We started with differential scanning calorimetry (DSC) analysis to gain information about the thermal tolerance threshold of our process and the thermal stability of 2-SF 5 -indoles (Figure A) . Both 2-SF 5 -indole 5a and 8 induce a strong release of energy (exothermic) when the threshold of thermal stability is reached, with enthalpies of −1180 kJ/kg with an onset above 165 °C for 5a and −1324 kJ/kg starting above 310 °C for 8 .…”
Section: Resultsmentioning
confidence: 99%
“…We then turned our attention to the reactivity of compound 7 in Diels–Alder cascades (Scheme ). Based on our previous activation strategy for pyrimidines, , we anticipated that acylation of the N7-atom from the hydrazone function with trifluoracetic anhydride should trigger a conformational switch of the side chain, bringing the 2-azadiene (the C2C5 moiety of the pyrazine ring) in close proximity to the alkynyl dienophile, thus favoring the initial [4 + 2] cycloaddition. Indeed, upon treatment of 7a by trifluoroacetic anhydride and 3-pentanone (acting as a trap for the HCN liberated during the retro-[4 + 2] step, leading to the corresponding cyanohydrin) , in THF at 60 °C for 4 h, 6-aza-indazole 8a and 7-aza-indazole 9a were produced in a 78:22 ratio (after aqueous hydrolysis).…”
mentioning
confidence: 99%
“…Inspired by our recent investigations on the Diels–Alder cascade of pyrimidines, we report herein the straightforward synthesis of 6-aza-indazoles 8 or 7-aza-indazoles 9 as the major to exclusive cycloadducts via an intramolecular Diels–Alder cascade of pyrazine 7 (Scheme C). Compared to the current state-of-the-art, this reaction sequence is characterized by mild reaction conditions and a predictable selectivity depending on the nature of the pyrazine’s substitution.…”
mentioning
confidence: 99%